Analyze Failure Of An Electrostatic Precipitator Ash Transfer System (ESP) At Pltu Pangkalan Susu Operation Maintenance Unit (OMU) - Reksha; Adi Sastra Tarigan; Hamdani (INFOKUM, 2021)
An electrostatic precipitator is a technology that removes residual ash from burning before being released into the atmosphere. The ionization process occurs on to flue gas inside electrostatic precipitator which then collected by collecting plate. Flue gas ionization is one thing that affects the efficiency of an electrostatic precipitator. The purpose of this research was to understand the effect of an overhaul on the efficiency calculation of electrostatic precipitator in Banten 3 Lontar OMU Power Plant. This research uses quantitative research methods with descriptive statistical analysis techniques. The data source used is the performance test inspection report data as well as technical data on unit 2 electrostatic precipitator obtained from PLTU Pangkalan Susu Lontar Power Plant. Data will be analyzed based on the calculation of total efficiency and the inspections into the electrostatic precipitator which affect voltage efficiency. Based on the analysis of the data obtained, the total efficiency of the electrostatic precipitator and an increase in voltage applied into discharge electrode will increase dust removal of electrostatic precipitator’s efficiency. Based on inspection data of unit 2 electrostatic precipitator of PLTU Pangkalan Susu Lontar Power Plant, overhaul tends to results in increasing voltage value from 36.25 kV into 50.06 kV. The value of the total efficiency of unit 2 electrostatic precipitator after the overhaul is 76%.